2015
DOI: 10.1111/maec.12247
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional condition of two coastal rocky fishes and the potential role of a marine protected area

Abstract: Knowledge of the nutritional conditions of coastal commercial fish populations is key to understanding stock health status, and is essential when making reasonable exploitation and management plans. Here, we present the first results on the condition and feeding preferences of two coastal fish species, Diplodus sargus (Linnaeus, 1758) and Pagellus erythrinus (Linnaeus, 1758). Using stable isotope and biochemical analyses, we tested the potential effects of a marine protected area (MPA) and the occurrence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 99 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…The protection measures in the NTZ guarantee the preservation of these habitats and their fauna and potentially increase nutrition quality (D'Anna et al ., ; Gordoa & Molí, ). The latter aspect is confirmed by two studies analysing the overall and nutritional condition of D. sargus from two western Mediterranean reserves (Lloret & Planes, ; Viladrich et al ., ). It should also be mentioned that the specimens of D. sargus sargus analysed by Viladrich et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The protection measures in the NTZ guarantee the preservation of these habitats and their fauna and potentially increase nutrition quality (D'Anna et al ., ; Gordoa & Molí, ). The latter aspect is confirmed by two studies analysing the overall and nutritional condition of D. sargus from two western Mediterranean reserves (Lloret & Planes, ; Viladrich et al ., ). It should also be mentioned that the specimens of D. sargus sargus analysed by Viladrich et al .…”
Section: Discussionmentioning
confidence: 97%
“…It should also be mentioned that the specimens of D. sargus sargus analysed by Viladrich et al . () are partially included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the application of MPAs has positively influenced the nutritional condition of fish species of commercial interest (Viladrich et al 2016). The RD index and its derivatives are highly sensitive, which has made it possible to map the larval condition and establish favourable areas in relation to the NPFS.…”
Section: Discussionmentioning
confidence: 99%
“…The monitoring of the larval state in situ over time could be a useful tool for determining favourable breeding areas for the species and for developing a time series to assess the effects of climate change in these areas. Detecting these favourable areas and periods for larval survival makes a valuable contribution to the comprehensive management of a population subjected to fishing exploitation (Viladrich et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids (FAs) samples were analyzed following the methodology described by Rossi and Fiorillo (2010), Rossi et al (2006b), and Viladrich et al (2015). Five samples of approximately 10 mg (±0.1 mg) of dried biomass from the different experiments were dissolved in dichlorolmethane:methanol (3:1); the FAs were analyzed with a splitless injection technique using gas chromatography analysis performed with an instrument (Agilent Technologies 7820A GC) equipped with a DB-5 ms Agilent column (60 m length, 0.25 mm internal diameter and 0.25 lm phase thickness).…”
Section: Fatty Acid Analysismentioning
confidence: 99%